Synthetic Manipulation of Hybrid Perovskite Systems in Search of New and Enhanced Functionalities. Issue 19 (22nd September 2017) - Naphade, Rounak; Nagane, Satyawan; Bansode, Umesh; Tathavadekar, Mukta; Sadhanala, Aditya; Ogale, Satishchandra
Abstract: Over the past few years the organic–inorganic hybrid perovskite systems have emerged as a promising class of materials for photovoltaic and electroluminescent thin‐film device applications, in view of their unique set of tunable optoelectronic properties. Importantly, these materials can be easily solution‐processed at low temperatures and as such are amenable to facile molecular engineering. Thus, a variety of low‐dimensional forms and quantum structures of these materials can be obtained through strategic synthetic manipulations through small molecule incorporation or molecular ion doping. In this Minireview, we specifically focus on these approaches and outline the possibilities of utilizing these for enhanced functionalities and newer application domains. Abstract : The manipulation approach : We discuss the advances of synthetic manipulations of organic–inorganic hybrid perovskite‐based systems, covering the areas of thin films, single crystals, and quantum nanostructures (0 D quantum dots, 1 D nanowires, nanorods). We also discuss the challenges and the opportunities in this rapidly evolving field.